Mechanical Properties of Surimi Gel Added with Olive Leaf Extract Powder - Muh Ali Arsyad; Arham Rusli; Masahiro Ogawa (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2019)
Mechanical property is important factors in determining quality of surimi-based products. Plant phenolic compound has been used to improve mechanical properties of surimi gel. The aim of this study was to determine the effects of addition of olive leaf extract powder (OLEP) on the mechanical properties of surimi gel. Addition of OLEP that contained polyphenol of 1.9 mg GAE/g dry weight to surimi increased breaking stress and breaking strain of surimi gel. The breaking stress and breaking strain of surimi gel increased with increasing OLEP concentration. The addition of 0.2% OLEP increased the breaking stress of surimi gel by 13% and the breaking strain by 27%. The addition of 0.5% OLEP resulted in a 1.2 times increase in the breaking stress and breaking strain of surimi gel. Increasing breaking stress and breaking strain of surimi gel with the addition of OLEP is caused by the integration of additional crosslinks into the protein networks via polyphenols or their derivatives. Although the addition of OLEP had a detrimental effect on whiteness of surimi gel, OLEP is still a useful functional ingredient for improving mechanical properties of surimi gel products in which the color is not an important quality.